Diálogo entre saberes no Ensino de Ciências: a Astronomia Indígena na percepção de estudantes dos anos finais do Ensino Fundamental - Alves, Deisiane De Toni (2025)
The struggle of indigenous peoples for decision-making spaces has resulted in significant achievements in recent years. However, challenges in the educational field persist, in the face of processes developed from Eurocentric, universalist, homogeneous and monocultural perspectives of content, which perpetuate a hegemonic culture that devalues other ways of understanding, being and existing in the world, among them, that of indigenous peoples. With their knowledge rendered invisible, it was for a long time left in the background in Brazilian society, but it has much to contribute to the different areas of knowledge, including Natural Sciences, based on a dialogue between knowledges. To this end, a critical, humanizing, intercultural, decolonial and countercolonial education is necessary, a context in which Paulo Freire's ideas stand out, since the core of this is based on the unveiling of reality, which allows the rich culture of indigenous peoples to come to light. In Science Education, from the perspective of Indigenous Astronomy, it is possible to help students overcome perceptions that science deals only with Western scientific knowledge and that this overlaps with traditional indigenous knowledge. With this in mind, we seek to answer the following research problem: What elements structure the discourse of students in the last year of elementary school, based on the study of Indigenous Astronomy, in the dialogue between scientific knowledge and traditional indigenous knowledge? To this end, we developed a qualitative research, with an interpretative approach and descriptive, exploratory and propositional objectives. We based our research on bibliographical and field research and Freirean Action Research, in which 9th grade students from a school in the city of Cascavel/PR were the subjects of the research. We constructed the data through Questionnaires, Questions prepared by the students and the Logbook. For the analysis, we relied on Freirean Discourse Analysis, based on a Specific Analysis and a General Analysis. The results obtained in the Specific Analysis revealed that most students presented non-critical perceptions, associated with elements of the subcategories Intransitive consciousness and Naive transitive consciousness, in which the lack of critical reflection was evidenced, as well as elements associated with prejudice. Few students expressed critical perceptions, reflecting on the colonizing processes and the marginalization of traditional indigenous knowledge, associated with the subcategory Critical transitive consciousness. When investigating the students' prior knowledge, most reported not having studied content related to indigenous culture and indigenous astronomy. In the analysis of the questions elaborated by the students, non-critical perceptions and critical perceptions were evidenced, associated with the subcategory Naive curiosity and Epistemological curiosity. In the General Analysis, from the category Dialogues between knowledge, critical perceptions stood out, in which students emphasized the importance of the exchange of knowledge in Science Teaching, as a way of promoting respect, as well as the relevance of dialogue in educational processes. Finally, they emphasized the importance of solid teacher training, which keeps pace with the advances provided by the inclusion of cultural themes in the Science Teaching curriculum.